Acceptance of electronic democracy: an empirically validated approach. (15th October 2012) - Kollmann, Tobias; Kayser, Ina; Stöckmann, Christoph
The internet equips citizens worldwide with an innovative channel of democratic participation and makes governments more citizen-friendly and accountable. To address a gap in previous research, the overall aim of this article is to identify the factors that determine citizen acceptance of online political participation and, based on these factors, how online participation can be fostered. We first conduct a literature review to establish an acceptance model with IS and political science determinates to account for e-participation acceptance. Using structural equation modelling, we then empirically validate the explanatory power of our model and identify the significant predictors of online participation, which are Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Political Activity (PA), Civic Orientation (CO) and Political Recruitment (PR). Overall, this study contributes to research and practice by explicating how IS-related influence factors and those from a political participation background can be integrated to further the understanding of citizens' acceptance of e-democracy.